Coil-EEFL Tube as Supreme Incandescent Light Source with Zero Electric Power Consumption, Astronomical Quantum Efficiency, and Long Life (Global Journal of Science Frontier Research, 2016)
We have challenged the different way to the contribution to the green energy project (COP; conference of the particles). Our attention is the reduction of the electric power consumption of the lighting sources. After the critical review of the established incandescent lamps, we have developed coil-EEFL tube that is the light source with the zero power consumption. The coil-EEFL tubes emit the light with the internal DC electric power generator that isolates from the external driving circuit with the electron flow. The coil-EEFL tubes light up with zero power consumption of the external DC driving circuit. The electrons move from cathode and anode of the internal DC power generator with the astronomical quantum efficiency that is 10 13 visible photons (m 3 , s) -1 . All components in the inside of the coil-EEFL tubes conserve in the operation, promising the prolonging of the operation life longer than 10 6 hours. The developed coil-EEFL tubes may use as the incandescent lamp as the general illumination source, including the backlight of the LCD panels for the computers and TV sets. The developed coil-EEFL tubes may contribute to the COP with the different way from the considerations of the generation of the electric power by others.
Keywords: green energy; FL tube; quantum efficiency; power consumption of lighting devices